Method for high-throughput screening of multi-element high-toughness amorphous alloy
Through the configuration entropy screening method based on X-ray energy spectroscopy analysis, the problem of long-time and high cost in screening amorphous alloy components with large fracture toughness in the existing technology has been solved, and an efficient and rapid screening process has been achieved, with significant efficiency improvement.
Patent Information
- Application Number
- CN202411745980.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, when screening amorphous alloy components with large fracture toughness, the method takes a long time, is costly and has low efficiency. Especially when the screening range is too large, the traditional nano-indentation method test time is too long, making it difficult to ensure continuous experiments. .
The configuration entropy screening method based on X-ray energy spectroscopy was used to prepare a multi-element strong and tough amorphous alloy thin film sample library through physical vapor phase multi-target co-sputtering deposition. The chemical composition distribution of the sample library was measured, the configuration entropy was calculated, and the configurations were screened out. Chemical composition of amorphous alloys with high type entropy.
This method significantly shortens the test time. Compared with the traditional nanoindentation method, the efficiency is increased by more than 20 times. Energy spectrum analysis is a non-destructive test, which ensures the integrity of the sample. The sample can be reused and is suitable for other performance tests.
Smart Images

Figure CN119334995A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of mechanical property testing and analysis, and in particular to a method for high-throughput screening of multi-component strong-toughness amorphous alloys. Background Art
[0002] Amorphous alloy is a new type of alloy different from traditional alloy materials. Its outstanding mechanical, physical, and chemical properties have attracted much attention in the field of engineering applications. As a new type of alloy with a disordered atomic structure, the rich physical phenomena contained in amorphous alloys have also attracted much attention in the field of basic research. However, room temperature brittleness has always restricted the practical application of amorphous alloys in structural engineering materials. At the same time, amorphous alloys are often composed of multiple elements, which brings huge challenges to composition optimization and performance modulation.
[0003] Fracture toughness is a mechanical property closely related to room temperature brittleness. Generally, a material system with greater fracture toughness will show excellent resistance to crack extension, which is crucial for the practical application of amorphous alloy materials. Therefore, the development of amorphous alloy systems with high fracture toughness has become one of the difficulties and hot spots in this field. However, currently only a few amorphous alloy component systems have high fracture toughness, and it is urgent to accelerate the process of screening new multi-component amorphous alloy materials with strong toughness.
[0004] The current testing methods for fracture toughness of materials are inseparable from indentation experiments, and all require information such as load-displacement curves and crack lengths. If the traditional trial-and-error method is used to screen strong multi-component tough amorphous alloy components, the workload is large, the cost is high, and the efficiency is low. In recent years, methods for high-throughput screening of amorphous fracture toughness have also been proposed. For example, the patented technology with the publication number CN116223760A previously applied for by the applicant mainly uses a physical vapor deposition co-sputtering method to deposit multiple alloy elements on a substrate to obtain a high-throughput sample library with a composition gradient. Subsequently, multiple indentation test points are set on the surface of the high-throughput sample library, and the fracture toughness value is obtained by calculation, thereby screening out the alloy component with the largest fracture toughness. Compared with the past methods, this patented technical method does shorten the research cost, but when the screening range is too large, this method is still relatively time-consuming. Taking 30 groups of test points as an example, in order to ensure the accuracy of the test, 6 nanoindentations are pressed at one test point, which will take 40-45 minutes of testing time. 30 groups will require more than 20 hours, and it is not easy to ensure continuous experiments. Therefore, in order to obtain alloy components with high fracture toughness more quickly, it is necessary to find a screening index that is more convenient and faster to characterize.
[0005] In crystalline alloys, the high mixing entropy (ΔS mix≥1.5R) can enhance the compatibility between alloy elements and inhibit the formation of ordered phases of intermetallic compounds. High entropy crystalline alloys have unique structures and excellent properties that some traditional alloys do not have. For example, high entropy alloys break the "curse" that strength and plasticity cannot be achieved at the same time, and have extremely high fracture toughness, good wear resistance and corrosion resistance. Some studies in recent years have shown that amorphous alloys also have the same "high entropy effect", that is, the greater the configuration entropy, the better the mechanical properties of the material. For example, Braic et al. deposited (CuSiTiYZr)C with an amorphous structure. x Carbide film. They found that with the increase of carbon content, the hardness gradually increased, and the hardness reached a maximum value of 29.5 GPa when the carbon content was 55.3at.%. High configurational entropy may be used to guide the preparation of fracture toughness of high-strength and tough amorphous alloys. At the same time, the calculation of configurational entropy requires testing the atomic percentage of each element in the amorphous alloy sample library, which can be obtained quickly and in large quantities using energy dispersive X-ray spectroscopy (EDS), which is convenient for high-throughput characterization. Therefore, configurational entropy can be used to perform high-throughput fracture toughness screening of amorphous alloys within a large component space. The present invention is thus formed. Summary of the invention
[0006] In the first aspect, the present invention provides a method for high-throughput screening of multi-component strong and tough amorphous alloys. Compared with the method of screening fracture toughness based on nanoindentation, the method proposed in the present invention is a configuration entropy screening method based on X-ray energy spectrum analysis, which is not only time-saving but also easy to operate. Taking 30 groups of test points as an example, it only takes 1 to 2 minutes to measure the alloy composition spectrum of one test point, and it only takes about 40 minutes to complete 30 groups, which is more than 20 times more efficient than the nanoindentation method. Moreover, energy spectrum analysis is a non-destructive test that ensures the integrity of the sample surface, and the sample can be reused for other performance tests.
[0007] A method for high-throughput screening of multi-component strong-toughness amorphous alloys, comprising: A sample library of multi-element strong and tough amorphous alloy films prepared by physical vapor multi-target co-sputtering deposition method; The chemical composition distribution of the sample library is measured by X-ray energy spectrum analysis, and the configuration entropy distribution of each local area in the sample library is obtained by calculation; The component of the amorphous alloy film with the largest configurational entropy is the chemical component of the amorphous alloy film with the best strength and toughness in the sample library.
[0008] The method of the present invention has the following characteristics: 1. The multi-element amorphous gradient film is prepared by physical vapor deposition multi-target co-sputtering method, which can obtain a "gene library" of amorphous films with a large composition range and multiple elements.
[0009] 2. X-ray energy spectrum analysis is used to characterize the chemical composition of each local area in the amorphous film sample library. The configuration entropy distribution of the sample library is obtained by calculation, and then the composition space of large fracture toughness is predicted.
[0010] 3. The nanoindentation energy conversion method can be further used to measure the fracture toughness distribution corresponding to the above sample library film to verify the reliability of the configuration entropy screening method of the present invention.
[0011] The present invention can determine the configuration entropy information of the amorphous alloy film sample library by measuring the component distribution of the amorphous alloy film sample library, and screen out the amorphous alloy chemical components with large configuration entropy, that is, the amorphous alloy chemical components with large fracture toughness. Furthermore, the fracture toughness can be verified by a measurement method based on the nanoindentation energy conversion method.
[0012] The method for high-throughput screening of multi-component strong-toughness amorphous alloys described in the first aspect can set multiple X-ray energy spectrum point scanning test points on the surface of the sample library, which can specifically include: dividing the surface of the sample library horizontally into multiple lateral regions, dividing any one or more lateral regions into multiple sub-regions, and selecting X-ray energy spectrum point scanning test points from each sub-region. By setting sub-regions, it is convenient to draw coordinate points on the surface of the sample library, so that the configuration entropy, alloy element content and subsequent fracture toughness values can be accurately matched. In some embodiments, each sub-region contains an amorphous alloy component with uniform distribution of chemical elements.
[0013] The method for high-throughput screening of multi-component strong-toughness amorphous alloys described in the first aspect can be calculated by the following formula (1) to obtain the configuration entropy: : (1), where is the gas constant, n is the number of elements that make up the amorphous alloy in the sample library, i are the element labels of the amorphous alloys in the sample library, For elements i The atomic percentage of amorphous alloys in the sample library. Further, 8.314 is acceptable .
[0014] In the method for high-throughput screening of multi-component strong-toughness amorphous alloys described in the first aspect, the roughness of the multi-component strong-toughness amorphous alloy film is preferably less than 5 nm.
[0015] In the method for high-throughput screening of multi-component strong-toughness amorphous alloys described in the first aspect, the thickness of the multi-component strong-toughness amorphous alloy film can be 100nm~10mm.
[0016] In the method for high-throughput screening of multi-component strong-toughness amorphous alloys described in the first aspect, the multi-component strong-toughness amorphous alloy film may be a Zr-Ti-Cu-Al amorphous alloy film. Further, in the Zr-Ti-Cu-Al amorphous alloy film, the Zr content may be 20at.%~33at.%, the Ti content may be 24at.%~27at.%, the Cu content may be 20at.%~30at.%, and the Al content may be 19at.%~29at.%.
[0017] In a second aspect, the present invention provides an application of the method described in the first aspect in high-throughput screening of multi-component strong-toughness amorphous alloys.
[0018] As a general inventive concept, in a third aspect, the present invention provides a multi-component strong and tough amorphous alloy, wherein, by atomic ratio, the composition of the multi-component strong and tough amorphous alloy is Zr 27 Cu 25 Ti 26 Al 22 .
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention sets multiple test points in the prepared amorphous alloy film sample library, uses an X-ray energy spectrum analyzer to measure the composition distribution of each test point, further calculates the configuration entropy, and uses the nano-continuous stiffness method and the nano-indentation energy conversion formula to obtain the fracture toughness of each indentation test point for verification. Based on the set test points, the configuration entropy of different areas in the amorphous film sample library is compared with the fracture toughness measured by the nano-indentation method to verify the reliability of the configuration entropy in reflecting the fracture toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of a physical vapor phase multi-target co-sputtering deposition sample library device provided for a specific embodiment of the present invention.
[0021] Figure 2 This is the element distribution diagram of the ZrTiCuAl quaternary high entropy amorphous alloy film sample library prepared in Example 1 of the present invention.
[0022] Figure 3 This is a configuration entropy distribution diagram of the sample library provided in Example 1 of the present invention.
[0023] Figure 4 This is a schematic diagram of the distribution of 29 circular sub-areas on the sample library provided in Example 1 of the present invention.
[0024] Figure 5 Schematic diagram of the process of the nanoindentation test performed in Example 1 of the present invention.
[0025] Figure 6This is the fracture toughness distribution diagram of the sample library of Example 1 of the present invention.
[0026] Figure 7 These are the four amorphous film components with relatively different fracture toughness selected in Example 1 of the present invention.
[0027] Figure 8 This is a corresponding relationship diagram between fracture toughness and configuration entropy in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0029] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.
[0030] A high-throughput screening and verification method for multi-element strong and tough amorphous alloy films, combined with Figure 1 , including the steps of: 1) A substrate and two or more target materials capable of forming an alloy are obtained, and a physical mask is disposed on the substrate.
[0031] 2) A multi-component gradient amorphous alloy film is deposited on the surface of a Si substrate using a physical vapor phase multi-target co-sputtering deposition technique to form a sample library. To reflect the high entropy effect, in Example 1, a zirconium-titanium-copper-aluminum quaternary alloy is taken as an example, and the alloy composition is: Zr (20at.%~33at.%), Ti (24at.%~27at.%), Cu (20at.%~30at.%), Al (19at.%~29at.%), wherein the percentage of each element is atomic percentage.
[0032] 3) Based on the horizontal and vertical coordinates of the sample library surface, multiple sub-regions are set, and the alloy element content corresponding to each sub-region is measured by energy dispersive spectroscopy analysis, and then the configuration entropy is calculated.
[0033] 4) Perform nanoindentation tests on each area to obtain the load-displacement curve and elastic modulus of the corresponding area, and calculate the fracture toughness according to the fracture toughness energy conversion formula (2)~(7) for verification.
[0034] The method for high-throughput screening and verification of multi-component strong-toughness amorphous alloy films can use the nanoindentation continuous stiffness method to perform indentation tests on each indentation test point, and use the nanoindentation energy conversion formula based on the indentation test results to obtain the fracture toughness value of each indentation test point. Furthermore, the obtained configuration entropy distribution of the film can be matched and verified with the fracture toughness value.
[0035] When the indenter used in the nanoindentation continuous stiffness method is a diamond indenter, the fracture toughness value of each indentation test point is obtained based on the indentation test results using the nanoindentation energy conversion formula. K c for: (2), (3), (4), (5), (6), (7), in, G c is the critical energy release rate corresponding to the occurrence of fracture, E r is the modulus, is irreversible energy, is the reversible energy, is the total energy, is the plastic energy, U f is the energy dissipated by fracture, is the contact area, is the maximum indentation depth, The depth of the indentation after removal of the unloading.
[0036] Specifically, the parameters of the nanoindentation test can be: the indentation depth is 9% to 10% of the alloy thickness in the sample library, there is no fixed indentation rate, the indentation load is 800 N, and the holding time is 10 s.
[0037] The nanoindentation probe used in the indentation test can be any one of a Bosch indenter, a Vickers indenter, and a spherical indenter. Example
[0038] 1. Preparation of Zr-Ti-Cu-Al quaternary high entropy amorphous alloy sample library: The sample library was prepared by physical vapor multi-target co-sputtering deposition, using pure zirconium (C target), titanium (D target), copper (A target) and aluminum (B target) metals, among which, Figure 1 As shown, pure zirconium (target C), copper (target A), and aluminum (target B) are 60° to the substrate, and pure titanium (target D) is perpendicular to the substrate. By adjusting the sputtering power of each target, target A is 32 W, target B is 25 W, target C is 45 W, and target D is 120 W. The sputtering parameters provided in the specific embodiment of the present invention are that the basic pressure in the chamber is less than 10 -5Pa, the working pressure is 0.3 Pa, and the flow rate of argon is 30 SCCM. The deposition time required for sample library preparation is 180 min.
[0039] 2. Perform X-ray spectrum analysis: For the sample library obtained in step 1 above, the content of each chemical element in the sample library is quantitatively tested by energy dispersive spectroscopy (EDS). In order to meet the requirements of mechanical properties testing, an atomic force microscope (AFM) is used for measurement. The roughness of the sample library is about 0.72 nm and the thickness is about 800 nm. Figure 2 The chemical composition gradient coverage of the sample library prepared in this example. Figure 2 As shown in Figure 1, zirconium is 20at.%~33at.%, titanium is 24at.%~27at.%, copper is 20at.%~30at.%, and aluminum is 19at.%~29at.%. According to the sample library component distribution and formula (1), the configuration entropy can be calculated step by step, as follows: Figure 3 shown.
[0040] The method provided in this embodiment for dividing the surface of the high-throughput sample library into circular sub-regions is as follows: the high-throughput sample library is divided into 29 circular sub-regions with a diameter of 4 mm, and the center distance between two adjacent circular sub-regions is 10 mm; a coordinate system is established with the sub-region at the center as the coordinate origin, such as Figure 4 shown.
[0041] 3. Use nanoindenter to test fracture toughness, such as Figure 5 As shown: Place the sample library obtained in step 1 flatly into the nanoindentation tester and fix it on the test platform to prevent the sample from sliding during the test; The nanoindentation instrument observed that the surface of the sample library was smooth and flat, ensuring that the mechanical properties test was carried out normally; The test parameters were adjusted to a surface approach speed of 15 nm / s, a holding time of 10 s, a Poisson's ratio of 0.367, and a continuous stiffness method. Based on a film thickness of 800 nm and a fixed indentation depth of 75 nm (e.g. Figure 5 As shown in the figure, an indentation test was carried out on each indentation test point, and the load-displacement curve of each indentation was recorded. The hardness was 5.5 GPa and the elastic modulus was 60 GPa.
[0042] The fracture toughness at different indentation test points is calculated according to the fracture toughness energy conversion formula of formulas (2) to (7). The fracture toughness of the three indentation test points in each sub-region is selected according to the one with the smaller error, that is, the elastic modulus obtained by nanoindentation is compared with the reference value (the reference value of the elastic modulus of the ZrTiCuAl alloy component in this case is 40~90GPa). The reasonable value measured at this data point is determined, and then its average value is calculated as the fracture toughness value of the region. The fracture toughness distribution corresponding to the sample library is obtained, as shown in the figure below: Figure 6 shown.
[0043] To illustrate the corresponding relationship, Figure 7 As shown, four points A to D are selected for analysis, and the conclusion is that the larger the material configuration entropy value, the greater the fracture toughness (such as Figure 8 As shown), it proves the reliability of the method of screening multi-component strong and tough amorphous alloys based on configuration entropy of X-ray energy spectrum analysis in the present invention.
[0044] The amorphous alloy film with the largest configuration entropy in this embodiment is composed of Zr 27 Cu 25 Ti 26 Al 22 (by atomic ratio), the region where it is located also has the largest fracture toughness according to nanoindentation testing.
[0045] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for high-throughput screening of multi-component strong and tough amorphous alloys, characterized in that: include: A sample library of multi-element strong and tough amorphous alloy films prepared by physical vapor multi-target co-sputtering deposition method; The chemical composition distribution of the sample library is measured by X-ray energy spectrum analysis, and the configuration entropy distribution of each local area in the sample library is obtained by calculation; The component of the amorphous alloy film with the largest configurational entropy is the chemical component of the amorphous alloy film with the best strength and toughness in the sample library.
2. The method according to claim 1, characterized in that A plurality of X-ray energy spectrum point scanning test points are set on the surface of the sample library, specifically including: dividing the surface of the sample library horizontally into a plurality of lateral regions, dividing any one or more lateral regions into a plurality of sub-regions, and selecting an X-ray energy spectrum point scanning test point from each sub-region.
3. The method according to claim 1, characterized in that The configuration entropy is calculated according to formula (1): : (1), where is the gas constant, n is the number of elements that make up the amorphous alloy in the sample library, i are the element labels of the amorphous alloys in the sample library, For elements i Atomic percentage of amorphous alloys in the sample library.
4. The method according to claim 3, characterized in that Take 8.314 .
5. The method according to claim 1, characterized in that The roughness of the multi-element strong-toughness amorphous alloy film is less than 5 nm.
6. The method according to claim 1, characterized in that The thickness of the multi-element strong-toughness amorphous alloy film is 100nm-10mm.
7. The method according to claim 1, characterized in that The multi-element strong-toughness amorphous alloy film is a Zr-Ti-Cu-Al amorphous alloy film.
8. The method according to claim 7, characterized in that In the Zr-Ti-Cu-Al amorphous alloy film, the Zr content is 20at.%-33at.%, the Ti content is 24at.%-27at.%, the Cu content is 20at.%-30at.%, and the Al content is 19at.%-29at.%.
9. Application of the method according to any one of claims 1 to 8 in high-throughput screening of multi-component strong-toughness amorphous alloys.
10. A multi-component strong and tough amorphous alloy, characterized in that: According to the atomic ratio, the composition of the multi-component tough amorphous alloy is Zr 27 Cu 25 Ti 26 Al 22 .
Citation Information
Patent Citations
Method for high-throughput screening of fracture toughness of amorphous alloy
CN116223760A
Cited By
High-throughput screening magnetron sputtering high-entropy alloy target material composition design method and target material
CN120519816A